2015
DOI: 10.1130/ges01077.1
|View full text |Cite
|
Sign up to set email alerts
|

Origin, structural geometry, and development of a giant coherent slide: The South Makassar Strait mass transport complex

Abstract: The South Makassar Strait mass transport complex (MTC) covers an area of at least 9000 km 2 and has a total volume of 2438 km 3 . It is composed of a shale-dominated sedimentary unit with high water content. Seismic refl ection data across the South Makassar Strait MTC show that it displays relatively coherent internal sedimentary stratigraphy that in the toe region is deformed into welldefi ned thrust-related structures (imbricates, ramps and fl ats, fault bend folds). It is one of the largest known coherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Considering that the two previous cases (the Storegga Slide and the study area) have similar turbidite rates, and other slope failures (volume > 1,000 km 3 ) located in deepwater regions with gentle slope gradients are similar to the northern South China Sea, the turbidite rates calculated in this work can be used as a reference to large slope failures. A large amount of turbidites (e.g., 1,890-5,292 km 3 for Makran Accretionary Complex) would therefore be expected in large-scale slope failures (see Table S2 for the possible turbidite contents of large-scale slope failures [imaged volume ≥ 1,000 km 3 ]; Armandita et al, 2015;Burg et al, 2008;Calvès et al, 2015;Chaytor et al, 2010;Collot et al, 2001;Denne et al, 2013;Dingle, 1977Dingle, , 1980Frey-Martinez et al, 2005;Gee et al, 2006;Haflidason et al, 2004;Hjelstuen et al, 2007;Lamarche et al, 2008;Lee et al, 2004;Leslie & Mann, 2016;Mosher et al, 2012;Niemi et al, 2000;Owen et al, 2010;Piper et al, 1997;Popenoe et al, 1993;Torelli et al, 1997;Trincardi & Argnani, 1990;Vanneste et al, 2006;Wynn et al, 2000). It is worth to note that there are still some uncertainties about the volume estimates for turbidites in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the two previous cases (the Storegga Slide and the study area) have similar turbidite rates, and other slope failures (volume > 1,000 km 3 ) located in deepwater regions with gentle slope gradients are similar to the northern South China Sea, the turbidite rates calculated in this work can be used as a reference to large slope failures. A large amount of turbidites (e.g., 1,890-5,292 km 3 for Makran Accretionary Complex) would therefore be expected in large-scale slope failures (see Table S2 for the possible turbidite contents of large-scale slope failures [imaged volume ≥ 1,000 km 3 ]; Armandita et al, 2015;Burg et al, 2008;Calvès et al, 2015;Chaytor et al, 2010;Collot et al, 2001;Denne et al, 2013;Dingle, 1977Dingle, , 1980Frey-Martinez et al, 2005;Gee et al, 2006;Haflidason et al, 2004;Hjelstuen et al, 2007;Lamarche et al, 2008;Lee et al, 2004;Leslie & Mann, 2016;Mosher et al, 2012;Niemi et al, 2000;Owen et al, 2010;Piper et al, 1997;Popenoe et al, 1993;Torelli et al, 1997;Trincardi & Argnani, 1990;Vanneste et al, 2006;Wynn et al, 2000). It is worth to note that there are still some uncertainties about the volume estimates for turbidites in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the timing and distribution of gravitydriven deposition has been used to reconstruct the tectonosedimentary evolution of passive (e.g. Armandita, Morley, & Rowell, 2015;Clark et al, 2012;Gamboa, Alves, Cartwright, & Terrinha, 2010;Heinio & Davies, 2006;Scarselli et al, 2016;Thöle, Kuhlmann, Lutz, & Gaedicke, 2016), and active margins (e.g. Alfaro & Holz, 2014;Covault, Romans, Graham, Fildani, & Hilley, 2011;Normark, Piper, & Sliter, 2006;Pérez et al, 2016;Richardson, Davies, Allen, & Grant, 2011;Romans, Normark, McGann, Covault, & Graham, 2009;Romero-Otero, Slatt, & Pirmez, 2010;Schwenk & Spieß, 2009;Sømme, Piper, Deptuck, & Helland-Hansen, 2011;Vinnels, Butler, McCaffrey, & Paton, 2010;Völker, Geersen, Behrmann, & Weinrebe, 2012).…”
mentioning
confidence: 99%
“…From quick inspection of the MTD the transport direction is not immediately apparent. Many seismic reflection‐based studies of MTDs have identified various kinematic indicators that can help constrain the direction, magnitude and mode of transport and classify MTDs (Frey‐Martinez et al ., ; Moscardelli & Wood, ; Bull et al ., ; Armandita et al ., ). Different kinematic indicators occur in the three classic domains of MTDs (Fig.…”
Section: Morphology Of the Mass Transport Depositsmentioning
confidence: 97%
“…The kinematic indicators typically associated with this domain are the presence of oblique and lateral ramps, with oblique displacement or strike‐slip senses of motion (e.g. Frey‐Martinez et al ., ; Bull et al ., ; Armandita et al ., ). Internally the translational domain can be chaotic, exhibit a mixture of thrust and extensional structures, or be a relatively undeformed domain that has undergone lateral translation on the basal detachment.…”
Section: Morphology Of the Mass Transport Depositsmentioning
confidence: 97%
See 1 more Smart Citation